Complementary Effect of Mungbean Sprouts on Growth Performance of Broiler Chickens - Lacuas, Richelle C.; Bacongco, Jundil A.; Oñal, Jr., Paulino A; Oñal, Paulino Miguel M. (Future Science / FSH-PH Publications, 2026)
The profitability of any chicken industry can always be correlated with increasing production. In the Philippines, as of the first quarter of 2022, poultry production had expanded by 12.3% because Filipino’s diet relies heavily on meat, thus placing livestock and poultry among essential segments of the country’s agriculture. The study aims to determine the level of mungbean sprouts that can complement the commercial feeds, which can ultimately improve the weekly body gain weight (WBGW) of broiler chickens and low feed conversion ratio (FCR). The study used the standard Complete Randomized Design (CRD) with four treatments and three replications. The mung beans were prepared in advance, taking care every day. The sprouting period of mung beans took about a week. Significant differences were revealed among treatments. Analysis of Variance implied that broiler chickens whose feed ration was complemented with 15% of mungbean sprouts had the highest WBGW of 546,67 grams and the lowest FCR of 1.74 at 28 days, respectively. The study recommends mixing 15% mungbean sprouts into the feed ration of broiler chickens for up to 28 days to improve the weight gain.